DAMP-Inducing Adjuvant and PAMP Adjuvants Parallelly Enhance Protective Type-2 and Type-1 Immune Responses to Influenza Split Vaccination - Hayashi, Tomoya; Momota, Masatoshi; Kuroda, Etsushi; Kusakabe, Takato; Kobari, Shingo; Makisaka, Kotaro; Ohno, Yoshitaka; Suzuki, Yusuke; Nakagawa, Fumika; Lee, Michelle S. J.; Coban, Cevayir; Onodera, Risako; et al. (Frontiers in Immunology, 2018)
Recently, it was reported that 2-hydroxypropyl-beta-cyclodextrin (HP-beta-CyD), a common pharmaceutical additive, can act as a vaccine adjuvant to enhance protective type-2 immunogenicity to co-administered seasonal influenza split vaccine by inducing host-derived damage-associated molecular patterns (DAMPs). However, like most other DAMP-inducing adjuvants such as aluminum hydroxide (Alum), HP-beta-CyD may not be sufficient for the induction of protective type-1 (cellular) immune responses, thereby leaving room for improvement. Here, we demonstrate that a combination of HP-beta-CyD with a humanized TLR9 agonist, K3 CpG-ODN, a potent pathogen-associated molecular pattern (PAMP), enhanced the protective efficacy of the co-administered influenza split vaccine by inducing antigen-specific type-2 and type-1 immune responses, respectively. Moreover, substantial antigen-specific IgE induction by HP-beta-CyD, which can cause an allergic response to immunized antigen was completely suppressed by the addition of K3 CpG-ODN. Furthermore, HP-beta-CyD- and K3 CpG-ODN-adjuvanted influenza split vaccination protected the mice against lethal challenge with high doses of heterologous influenza virus, which could not be protected against by single adjuvant vaccines. Further experiments using gene deficient mice revealed the unique immunological mechanism of action in vivo, where type-2 and type-1 immune responses enhanced by the combined adjuvants were dependent on TBK1 and TLR9, respectively, indicating their parallel signaling pathways. Finally, the analysis of immune responses in the draining lymph node suggested that HP-beta-CyD promotes the uptake of K3 CpG-ODN by plasmacytoid dendritic cells and B cells, which may contributes to the activation of these cells and enhanced production of IgG2c. Taken together, the results above may offer potential clinical applications for the combination of DAMP-inducing adjuvant and PAMP adjuvant to improve vaccine immunogenicity and efficacy by enhancing both type-2 and type-1 immune responses in a parallel manner.